Pengaruh Capital Adequacy Ratio, Net Profit Margin, dan Kepemilikan Institusional Terhadap Kebijakan Dividen pada Perusahaan Perbankan yang Terdaftar di BEI Periode 2018-2022: Capital Adequacy Ratio, Net Profit Margin, Kepemilikan Institusional, dan Kebijakan Dividen - Machfud Purnomo dan Arba'atoen, Rafi Muhammad Faqih; Gede Adi Yuniarta (Vokasi : Jurnal Riset Akuntansi, 2024)
This research aims to determine the influence of Capital Adequacy Ratio, Net Profit Margin, and institutional ownership on dividend policy in banking companies listed on the IDX for the 2018-2022 period. The population of this research is 47 banking companies listed on the IDX for the 2018-2022 period. In this research, the sampling technique used was purposive sampling, so the number of samples used in this research was 12 companies. The data collection method uses documentation studies by taking annual financial report data and banking Dividend Payout Ratio. Data analysis in this study used multiple linear regression analysis using the SPSS version 21 for Windows program. The research results show that: (1) Capital Adequacy Ratio has a negative effect on dividend policy, (2) Net Profit Margin has a negative effect on dividend policy. (3) institutional ownership has a negative effect on dividend policy.